Analisis Potensi Ekstrak Belimbing Wuluh (Averrhoa Bilimbi L.) terhadap Kematian Larva Aedes Albopictus Di Laboratorium Balai Litbangkes Tanah Bumbu - Siti Mahfiroh; Norfai Norfai; Zuhrupal Hadi (Jurnal Kesehatan Indonesia, 2023)
DHF is an endemic disease that occurs throughout the year. Efforts to control DHF still using chemical insecticides that can cause resistance and have negative. The use of vegetable insecticides from plants can be an alternative to natural larvicides, one of which is starfruit (Averrhoa bilimbi L.) which has the potential as an insecticide due to the presence of toxic substances. The purpose of this study was to analyze mortality, the difference in the average mortality of Aedes Albopictus larvae and to determine the Lethal Time and Lethal Concentration. This type of research is a quantitative research with the True Experimental Design method with Posttest Only Group Design. The results showed that 100% larval death was the fastest at a concentration of 8% after 4 hours of measurement. The results of the Kruskall Wallis test showed that there was no significant difference (>0.05) in the average mortality of larvae. The results of the Lethal Time probit test showed that it took 2,029 hours to kill 50% of larvae and 4,551 hours to kill 99% of larvae with a concentration of 8% while the Lethal Concentration showed that a concentration of 2.647% was needed to kill 50% of larvae and 7.854% to kill 99%. larvae. Further research is needed to develop starfruit extract (Averrhoa bilimbi L.) which, when applied to water, is colorless and tasteless, but does not remove the compounds present in starfruit extract.